2012
DOI: 10.1111/j.1751-1097.2012.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Level Laser Therapy Restores the Oxidative Stress Balance in Acute Lung Injury Induced by Gut Ischemia and Reperfusion

Abstract: It remains unknown if the oxidative stress can be regulated by low-level laser therapy (LLLT) in lung inflammation induced by intestinal reperfusion (i-I/R). A study was developed in which rats were irradiated (660 nm, 30 mW, 5.4 J) on the skin over the bronchus and euthanized 2 h after the initial of intestinal reperfusion. Lung edema and bronchoalveolar lavage fluid neutrophils were measured by the Evans blue extravasation and myeloperoxidase (MPO) activity respectively. Lung histology was used for analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 51 publications
5
39
0
1
Order By: Relevance
“…The anti-oxidant effect of LC is thought to be due its ability to increase the activity of antioxidant enzymes [20,21]. Laser therapy restores the balance between oxidants and antioxidants [22]. This is in agreement with the laser-induced significant increases in antioxidant parameters seen in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The anti-oxidant effect of LC is thought to be due its ability to increase the activity of antioxidant enzymes [20,21]. Laser therapy restores the balance between oxidants and antioxidants [22]. This is in agreement with the laser-induced significant increases in antioxidant parameters seen in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The de Lim et al study carried out on rats could be an example. After the low-level laser irradiating, an increased level of reduced glutathione was observed (wavelength λ = 660 nm, power 30 mW, energy 5.4 J), which suggests antioxidant properties of the irradiation [12]. The results of this study prove the effect of LLLT on the GSH levels in human, which was previously observed only in animal models.…”
Section: Discussionsupporting
confidence: 70%
“…19,21,22 This photodissociation would allow oxygen fixation and thereby enhance cellular respiration and metabolism. This type of treatment has been shown to reduce production of factors associated with oxidative stress in various cell types in vitro as well as in affected tissues of laboratory animals with experimentally induced ischemiareperfusion injury or age-related retinal changes 21,[23][24][25][26] and to protect against oxidative stress by activating scavenging superoxide anions. 27 In rats with blunt-impact muscle trauma, photobiomodulation therapy blocked reactive oxygen species release and activation of nuclear factor-kB, inhibited overexpression of inducible nitric oxide synthase, reduced the inflammatory response, and decreased collagen production in the traumatized muscle, compared with traumatized muscles from rats that did not undergo photobiomodulation therapy.…”
Section: Ivddmentioning
confidence: 99%